The importance of melanoma inhibitory activity gene family in the tumor progression of oral cancer - Sasahira, Tomonori; Boßerhoff, Anja Katrin; Kirita, Tadaaki (Pathology International, 2018)
Oral squamous cell carcinoma has a high potential for locoregional invasion and nodal metastasis. Consequently, early detection of such malignancies is of immense importance. The melanoma inhibitory activity (MIA) gene family comprises MIA, MIA2, transport and Golgi organization protein 1 (TANGO), and otoraplin (OTOR). These members of the MIA gene family have a highly conserved Src homology 3 (SH3)-like structure. Although the molecules of this family share 34-45% amino acid homology and 47-59% cDNA sequence homology, those members, excluding OTOR, play different tumor-associated functions. MIA has a pivotal role in the progression and metastasis of melanoma; MIA2 and TANGO have been suggested to possess tumor-suppressive functions; and OTOR is uniquely expressed in cochlea of the inner ear. Therefore, the definite functions of the MIA gene family in cancer cells remain unclear. Since the members of the MIA gene family are secreted proteins, these molecules might be useful tumor markers that can be detected in the body fluids, including serum and saliva. In this review, we described the molecular biological functions of the MIA gene family in oral cancer.
EVALuna2:34285